2021
DOI: 10.3389/feduc.2021.690646
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned: Teaching In-Person During the COVID-19 Pandemic

Abstract: For the Fall 2020 semester, the University of New Haven (UNewHaven) joined over a third of colleges and universities across the country in offering in-person courses and reopening its campus. Allowing the campus community to safely return was a challenging endeavor, particularly for those at the University’s School of Health Sciences, which offers both non-clinical and clinical courses. In order to create learning environments that adhered to continuously-changing guidelines, our team at the School of Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…During the COVID-19 pandemic, precarious circumstances for teaching and researching in academia made the relevance of emotional states and mental health of academic staff more obvious (Tran et al, 2021). The study of Tran et al (2021) focused the emotional state of the academic staff on a broader level without concrete emotion theories as basis.…”
Section: Emotional Experiences In Academiamentioning
confidence: 99%
See 4 more Smart Citations
“…During the COVID-19 pandemic, precarious circumstances for teaching and researching in academia made the relevance of emotional states and mental health of academic staff more obvious (Tran et al, 2021). The study of Tran et al (2021) focused the emotional state of the academic staff on a broader level without concrete emotion theories as basis.…”
Section: Emotional Experiences In Academiamentioning
confidence: 99%
“…Previous research argues that scientific discoveries are impossible without emotions (Fischer et al, 2014). Tran et al (2021) showed in their study that academic staff often reached their workload limits due to continuously changing requirements for academic work including research and teaching during the COVID-19 pandemic. Resulting from the circumstances during the pandemic, faculty begun to increasingly evaluate the emotional state of their academic staff (Tran et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations